APLIKASI PENGENALAN ULAR ASLI PULAU JAWA BAGI PARA PENCINTA REPTIL (Information Technology and Telematics, 2013)
Snakes are one of a kind reptiles that have many features of patterns and characteristics, this reason adding exoticism of them. But unfortunately most of the people still think that snakes are horrific and disgusting animals, so it’s important to introduce to the public about the types of snakes around us both venomous and non-venomous snakes. From this case the writer is trying to take an opportunity to apply using computer science-based on multimedia application so it can be used in daily life. Multimedia is a tool that can create a dynamic and interactive presentation combines text, graphics, animation, audio and video.From that combination that will be made an original java snakes introduction application for reptile lovers understand the types of snakes so there’s no mistakes in recognizing and maintaining the snakes. This application is developed using multimedia research methodology which are consists of several stages, concept, design, collecting material, assembly, testing, and distribution. Using Adobe Flash CS5 as a main software for make this application.From the results of processing this application found that Sahabat Reptil Indonesia as a case study responded well with this application because this application is easy to understand and very interesting.Keywords : multimedia, snake, reptile, Adobe Flash.